Correlation between Matrix Metalloproteinase-9 (MMP-9) Serum Levels and Alteration of NIHSS Score in Acute Ischemic Stroke - Riasari, Naili Sofi; Tugasworo, Dodik; Husni, Amin (International Journal of Human and Health Sciences (IJHHS), 2022)
Objective : MMP-9 is a proteolytic enzyme that plays a role in stroke pathological process. Its secretion increases rapidly after ischemic stroke onset. It gives a promising biomarker of stroke prognosis.The NIHSS (National Institute of Health Stroke Scale) is a clinical scale for predicting post stroke clinical outcomes. The study aim is to determine the correlation between MMP-9 serum levels and alteration of NIHSS score in acute ischemic stroke. Material and Methods :This was a prospective cohort study at Kariadi Hospital Semarang during October 2018 - January 2019. Subjects met the inclusion and exclusion criteria were taken for 5 cc venous blood samples ≤48 hours of stroke onset to examine the MMP-9 serum levels andmeasured alteration of NIHSS scores between the 2nd, 7thand 14th day of stroke onset. Results : There were 51 subjects with a mean MMP-9 serum levels of 1.223,24 ng/ml (normal 169-705 ng/ml). Elevated MMP-9 serum levels were correlated with worsening clinical outcomes on 7th and 14th day of stroke onset (p=0.007 ; p=0.005). ROC curve analysis obtained MMP-9 serum levels ≤48 hours of stroke onset with a cutoff point of 899.5 ng/ml, which MMP-9 serum levels above 899.5 ng/ml as a predictor of worsening clinical outcome. Conclusion :There was correlation between MMP-9 serum levels ≤48 hours of ischemic stroke onset with clinical outcome on 7th and 14th day of stroke onset. International Journal of Human and Health Sciences Vol. 06 No. 02 April’22 Page: 208-212